Uganda : Managing More Effective Decentralization - Brosio, Giorgio (IMF Working Papers; Working Paper, 2006)
This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. A politically driven and ambitious decentralization program implemented by the authorities since the late 1990s has had mixed results in terms of enhancing service delivery. Paradoxically, concerns with the results of service delivery, partially driven by donors' requirements, have resulted in a deconcentrated system relying on conditional grants and unfunded mandates. This has reduced the incentives, responsibility, and ownership for local authorities to improve service delivery. Crucially, for functions where the local authorities have had full responsibility, better service quality has resulted than in those areas in which there are overlapping responsibilities between the center and the local authorities.